A Taqriz for a Nineteenth Century Indonesian Manuscript - Kaptein, Nico J.G. (Center for Research and Development of Religious Literature and Heritage, 2015)
In medieval Arabic literature, a taqrīẓ is a written endorsement of a certain text, provided by a prestigious scholar at the request of another scholar to support the latter’s new writing. In this sense, it can be likened to the contemporary